2020
DOI: 10.1101/2020.10.10.20210070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe COVID-19 patients display a back boost of seasonal coronavirus-specific antibodies

Abstract: Severe acquired respiratory syndrome coronavirus-2 (SARS-CoV-2) is the cause of coronavirus disease (COVID-19). In severe COVID-19 cases, higher antibody titers against seasonal coronaviruses have been observed than in mild cases. To investigate antibody cross-reactivity as potential explanation for severe disease, we determined the kinetics, breadth, magnitude and level of cross-reactivity of IgG against SARS-CoV-2 and seasonal CoV nucleocapsid and spike from 17 severe COVID-19 cases at the clonal level. Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
(81 reference statements)
4
39
0
Order By: Relevance
“…Such responses have been shown for influenza and dengue virus and are associated with poor virus neutralization and can have profound consequences on vaccine efficacy (190)(191)(192)(193). For SARS-CoV-2 infections, a number of studies have now reported back-boosting of non-neutralizing sCoV antibody production (116,118,167,194,195). These antibodies appear to be most prominently targeted against conserved epitopes in OC43 and HKU1, both betacoronaviruses (194,195).…”
Section: Immunological Back-boosting By Scov Antibodies and The Origimentioning
confidence: 99%
See 2 more Smart Citations
“…Such responses have been shown for influenza and dengue virus and are associated with poor virus neutralization and can have profound consequences on vaccine efficacy (190)(191)(192)(193). For SARS-CoV-2 infections, a number of studies have now reported back-boosting of non-neutralizing sCoV antibody production (116,118,167,194,195). These antibodies appear to be most prominently targeted against conserved epitopes in OC43 and HKU1, both betacoronaviruses (194,195).…”
Section: Immunological Back-boosting By Scov Antibodies and The Origimentioning
confidence: 99%
“…For SARS-CoV-2 infections, a number of studies have now reported back-boosting of non-neutralizing sCoV antibody production (116,118,167,194,195). These antibodies appear to be most prominently targeted against conserved epitopes in OC43 and HKU1, both betacoronaviruses (194,195). Interestingly, none of these studies presented evidence that a sCoV antibody boost was associated with either protection against SARS-CoV-2 infection or COVID-19 severity.…”
Section: Immunological Back-boosting By Scov Antibodies and The Origimentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42] Alternatively, these preexisting crossreactive antibodies could interfere with the development and/or maintenance of effective levels of anti-SARS-CoV-2 antibodies 43,44 and, even worse, they could have a negative impact by mediating antibody-dependent disease enhancement (ADE), 45,46 which could be associated with severe prognosis. 47,48 Our study aimed to better characterize the immunogenicity, specificity and crossreactivity of anti-N antibodies from SARS-CoV-2 and 229E, HKU1, NL63, and OC43 HCoV, measured simultaneously. To this end, we tested several antigenic fragments in multiplex to measure different immunoglobulin (Ig) isotypes, and compared their relative immunogenicity in prepandemic and pandemic samples, including SARS-CoV-2 positive cases.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactive antibodies between endemic human coronaviruses (HCoV) and SARS-CoV-2 have been widely reported ( 27, 28 ), suggesting past exposure to HCoVs may prime ADCC and ADP immunity against SARS-CoV-2. In addition, several studies have shown back-boosting of antibodies against endemic human coronaviruses (HCoV) following infection with SARS-CoV-2 ( 29, 30 ), likely due to the recall of pre-existing B cell responses against conserved regions of S. We thus determined whether IgG antibodies against S from four HCoV strains (OC43, HKU1, 229E and NL63) (Table S2) were boosted in COVID-19 convalescent subjects compared to uninfected healthy controls. We found that COVID-19 convalescent subjects had increased IgG antibodies against S from the betacoronaviruses OC43 and HKU1 (that are more closely related to SARS-CoV-2) at the first timepoint sampled compared to uninfected controls (Fig S7), while there was no difference in IgG levels against S from the alphacoronaviruses 229E and NL63.…”
Section: Resultsmentioning
confidence: 99%